Acquisition and interpretation of radiographs of the equine skull. (17th September 2013) - Barrett, M. F.; Easley, J. T.
Summary: The complex anatomy of the equine skull creates a radiographic challenge. However, radiographs are a commonly required tool in diagnosing dental and sinonasal disease, as well as other disorders of the equine skull. High quality, complete radiographic studies are essential for adequate evaluation. Radiographic technique and interpretation are reviewed in this paper.